Resolving the Financial Crisis: Are We Heeding the Lessons from the Nordics? - Claudio Borio; Bent Vale; Goetz von Peter (Norges Bank, 2010)
How does the management and resolution of the current crisis compare with the response of the Nordic countries in the early 1990s, widely regarded as exemplary? We argue that, while intervention has been prompter, the measures taken so far remain less comprehensive and in-depth. In particular, the cleansing of balance sheets has proceeded more slowly, and less attention has been paid to reducing excess capacity and avoiding competitive distortions. In general, policymakers have given higher priority to sustaining aggregate demand in the short term than to encouraging adjustment in the financial sector and containing moral hazard. We argue that three factors largely explain this outcome: the more international nature of the crisis; the complexity of the instruments involved; and, hardly appreciated so far, the effect of accounting practices on the dynamics of the events, reflecting in particular the prominent role of fair value accounting (and mark to market losses) in relation to amortised cost accounting for loan books. There is a risk that the policies followed so far may delay the establishment of the basis for a sustainably profitable and less risk-prone financial sector.
hdl:11250/2497446
Keywords: G01; G21; G28; 330; crisis management and resolution; principles for successful resolution; nordic countries; fair value and amortised cost accounting; mark to market losses